(3JPcQI GdeMHjf aj CSeGA SjO GdeQSdjfs - (3CHhYHO Gddg eMeO Hf bGSe GdCfUGQj GdJdeSGfj GdeYQha HGdnQnUGY,J (B894 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEfi QCjJ ef faSj GdEfTZGd HeG jZfjfi ef GdeSGFd LYdJ hSjdI Hjfi hHjf SjO GdeQSdjf hbO Cdgefj Gddg Edi TQM HYV CSeGA GdeUWai s
(3BNQgG (B:s
(3hjMTQfj hGdSGeYjf dgPG GdcJGH aj ReQI fHjfG eMeO Ydjg CaVd GdUdGI hGdSdGe ced HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B93 - (3U(B435s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B101 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(631 (3b(B) s
Keywords: (3GdJGQjNs